DESIGN DEVELOPMENT AND EVALUATION OF NANOSUSPENSION OF AZITHROMYCIN (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The objective of this study is to prepare a formulation of Azithromycin which increase the oral bioavailability as well as increased solubility and dissolution rate. In the present study nine formulations were formulated by using the three different polymers and varying the concentration of PEG and also varying the rotation speed of the stirrer. Results of preformulation studies like melting point 117°C, UV spectroscopy and FTIR studies showed that the drug was pure. The spherical and rough surface of F9 viewed through SEM. In-vitro dissolution study had shown satisfactory results. On the basis of release data and graphical analysis formulation F8 and F9 showed a good controlled zero order release profile.